"Catching your tail and firefighting": The impact of staffing levels on restraint minimization efforts. Issue 5 (19th June 2019) - McKeown, Mick; Thomson, Gill; Scholes, Amy; Jones, Fiona; Baker, John; Downe, Soo; Price, Owen; Greenwood, Paul; Whittington, Richard; Duxbury, Joy
Accessible summary: What is known on the subject?: Mental health nursing in the UK and other countries faces an acute workforce crisis. Safe staffing levels are called for, and in some jurisdictions have been legislated for. The evidence base linking staffing levels and patient outcomes is limited. Staffing levels are implicated in adverse experiences of service users and staff within mental health ward settings, and they might contribute to levels of violence and aggression and the application of restrictive practices, such as physical restraint but there is limited research evidence to support this. Programmes such as Safewards, No Force First, the Engagement Model and the Six Core Strategies can reduce the use of restrictive practices. What does this paper add to existing knowledge?: Staffing levels on acute mental health wards appeared crucial in the implementation of a restraint minimization project. Both staff and service users implicate insufficient staffing for deficiencies in the relational elements of care, such as lack of face‐to‐face contact between nurses and service users. Similarly, staffing levels are associated with perceived problems in the cause of violence and aggression and responses to it. Despite successes in minimizing restrictive practices in this project, difficulties implementing alternative forms of practice that would reduce use of physical restraint, such as de‐escalation, were also attributed to staffing levels. There is an irony that a project concerned with safety itself provoked concern over safe staffing levels. What are the implications for practice?: Efforts to reduce restrictive practices will be hampered without adequate staffing levels. Restrictive practices may justifyably be framed as an employment relations matter. Organisations and policy makers ought to address environmental, contextual and resourcing factors, rather than identify problems exclusively in terms of perceived aberrant behaviour of staff or service users. Abstract: Introduction: Safe staffing and coercive practices are of pressing concern for mental health services. These are inter‐dependent, and the relationship is under‐researched. Aim: To explore views on staffing levels in a context of attempting to minimize physical restraint practices on mental health wards. Findings emerged from a wider data set with the broader aim of exploring experiences of a restraint reduction initiative. Methods: Thematic analysis of semi‐structured interviews with staff ( n  = 130) and service users ( n  = 32). Results: Five themes were identified regarding how staffing levels impact experiences and complicate efforts to minimize physical restraint. We titled the themes—"insufficient staff to do the job"; "detriment to staff and service users"; "a paperwork exercise: the burden of non‐clinical tasks"; "false economies"; and, "you can't do these interventions." Discussion: Tendencies detracting from relational aspects of care are not independent of insufficiencies in staffing. The relational, communicative and organizational developments that would enable reductions in use of restraint are labour intensive and vulnerable to derailment by insufficient and poorly skilled staff. Implications for practice: Restrictive practices are unlikely to be minimized unless wards are adequately staffed. Inadequate staffing is not independent of restrictive practices and reduces access to alternative interventions for reducing individuals' distress.